Efficient use of coffee genetic resources: molecular analyses of genome interactions in the arabusta hybrid (Coffea arabica x C. canephora) - Herrera, J.C.; Combes, M.C.; Anthony, F.; Lashermes, P. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2014)
4 ilus. 1 tab. 7 ref.